Tri Pusat Pendidikan Sebagai lembaga Pengembangan Teori Pembelajaran - Misbahuddin Amin (JURNAL MAPPESONA, 2024)
The Tricenter of Education is three educational centers that gradually and integrally carry out an educational responsibility for children. The three education centers in question include education in the family environment, education in the school environment and education in the community environment. The three persons in charge of education are required to cooperate with each other comprehensively. The family environment, which is the first environment and is considered as the foundation of children's education, which is also the beginning of the education that will be pursued next, also plays a very important role in the formation of personality. The school environment is the second environment faced by children. Education in the school environment has a basis, objectives, content, methods and other requirements that are systematically arranged in the form of a curriculum. Therefore, schools are considered as laying the foundation of scientific knowledge. Meanwhile, in the community environment, children will realize a number of educational and teaching theories that have been taught in educational institutions before. Because after all, children will actualize and involve themselves in the community environment.